• <blockquote id="a6oys"></blockquote>
  • <tt id="a6oys"></tt>
  • Paul's Online Notes
    Paul's Online Notes
    Home / Calculus I / Extras / Proof of Various Integral Properties
    Show General Notice Show Mobile Notice Show All Notes Hide All Notes
    General Notice

    I apologize for the outage on the site yesterday and today. Lamar University is in Beaumont Texas and Hurricane Laura came through here and caused a brief power outage at Lamar. Things should be up and running at this point and (hopefully) will stay that way, at least until the next hurricane comes through here which seems to happen about once every 10-15 years. Note that I wouldn't be too suprised if there are brief outages over the next couple of days as they work to get everything back up and running properly. I apologize for the inconvienence.

    Paul
    August 27, 2020

    Mobile Notice
    You appear to be on a device with a "narrow" screen width (i.e. you are probably on a mobile phone). Due to the nature of the mathematics on this site it is best views in landscape mode. If your device is not in landscape mode many of the equations will run off the side of your device (should be able to scroll to see them) and some of the menu items will be cut off due to the narrow screen width.

    Section 7-5 : Proof of Various Integral Properties

    In this section we’ve got the proof of several of the properties we saw in the Integrals Chapter as well as a couple from the Applications of Integrals Chapter.

    Separator

    Proof of : \(\int{{k\,f\left( x \right)\,dx}} = k\int{{f\left( x \right)\,dx}}\) where \(k\) is any number.

    This is a very simple proof. Suppose that \(F\left( x \right)\) is an anti-derivative of \(f\left( x \right)\), i.e. \(F'\left( x \right) = f\left( x \right)\). Then by the basic properties of derivatives we also have that,

    \[{\left( {k\,F\left( x \right)} \right)^\prime } = k\,F'\left( x \right) = k\,f\left( x \right)\]

    and so \(k\,F\left( x \right)\) is an anti-derivative of \(k\,f\left( x \right)\), i.e. \({\left( {k\,F\left( x \right)} \right)^\prime } = k\,f\left( x \right)\). In other words,

    \[\int{{k\,f\left( x \right)\,dx = k\,F\left( x \right) + c}} = k\int{{f\left( x \right)\,dx}}\]
    Separator

    Proof of : \(\int{{f\left( x \right) \pm g\left( x \right)\,dx}} = \int{{f\left( x \right)\,dx}} \pm \int{{g\left( x \right)\,dx}}\)

    This is also a very simple proof Suppose that \(F\left( x \right)\) is an anti-derivative of \(f\left( x \right)\) and that \(G\left( x \right)\) is an anti-derivative of \(g\left( x \right)\). So we have that \(F'\left( x \right) = f\left( x \right)\) and \(G'\left( x \right) = g\left( x \right)\). Basic properties of derivatives also tell us that

    \[{\left( {F\left( x \right) \pm G\left( x \right)} \right)^\prime } = \,F'\left( x \right) \pm G'\left( x \right) = f\left( x \right) \pm g\left( x \right)\]

    and so \(\,F\left( x \right) + G\left( x \right)\) is an anti-derivative of \(\,f\left( x \right) + g\left( x \right)\) and \(\,F\left( x \right) - G\left( x \right)\) is an anti-derivative of \(\,f\left( x \right) - g\left( x \right)\). In other words,

    \[\int{{f\left( x \right) \pm g\left( x \right)\,dx}} = F\left( x \right) \pm G\left( x \right) + c = \int{{f\left( x \right)\,dx}} \pm \int{{g\left( x \right)\,dx}}\]
    Separator

    Proof of : \(\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} = - \int_{{\,b}}^{{\,a}}{{f\left( x \right)\,dx}}\)

    From the definition of the definite integral we have,

    \[\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} \hspace{0.25in}\hspace{0.25in}\hspace{0.25in}\Delta x = \frac{{b - a}}{n}\]

    and we also have,

    \[\int_{{\,b}}^{{\,a}}{{f\left( x \right)\,dx}} = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} \hspace{0.25in}\hspace{0.25in}\hspace{0.25in}\Delta x = \frac{{a - b}}{n}\]

    Therefore,

    \[\begin{align*}\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} & = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\frac{{b - a}}{n}} \\ & = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\frac{{ - \left( {a - b} \right)}}{n}} \\ & = \mathop {\lim }\limits_{n \to \infty } \left( { - \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\frac{{a - b}}{n}} } \right)\\ & = - \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\frac{{a - b}}{n}} = - \int_{{\,b}}^{{\,a}}{{f\left( x \right)\,dx}}\end{align*}\]
    Separator

    Proof of : \(\int_{{\,a}}^{{\,a}}{{f\left( x \right)\,dx}} = 0\)

    From the definition of the definite integral we have,

    \[\begin{align*}\int_{{\,a}}^{{\,a}}{{f\left( x \right)\,dx}} & = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} \hspace{0.25in}\hspace{0.25in}\hspace{0.25in}\Delta x = \frac{{a - a}}{n} = 0\\ & = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\left( 0 \right)} \\ & = \mathop {\lim }\limits_{n \to \infty } 0\\ & = 0\end{align*}\]
    Separator

    Proof of : \(\int_{{\,a}}^{{\,b}}{{cf\left( x \right)\,dx}} = c\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}}\)

    From the definition of the definite integral we have,

    \[\begin{align*}\int_{{\,a}}^{{\,b}}{{c\,f\left( x \right)\,dx}} & = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {c\,f\left( {x_i^*} \right)\Delta x} \\ & = \mathop {\lim }\limits_{n \to \infty } c\sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} \\ & = c\mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} \\ & = c\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}}\end{align*}\]

    Remember that we can pull constants out of summations and out of limits.

    Separator

    Proof of : \(\int_{{\,a}}^{{\,b}}{{f\left( x \right) \pm g\left( x \right)\,dx}} = \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} \pm \int_{{\,a}}^{{\,b}}{{g\left( x \right)\,dx}}\)

    First we’ll prove the formula for “+”. From the definition of the definite integral we have,

    \[\begin{align*}\int_{{\,a}}^{{\,b}}{{f\left( x \right) + g\left( x \right)\,dx}} & = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {\left( {f\left( {x_i^*} \right) + \,g\left( {x_i^*} \right)} \right)\Delta x} \\ & = \mathop {\lim }\limits_{n \to \infty } \left( {\sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} + \sum\limits_{i = 1}^n {g\left( {x_i^*} \right)\Delta x} } \right)\\ & = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} + \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {g\left( {x_i^*} \right)\Delta x} \\ & = \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} + \int_{{\,a}}^{{\,b}}{{g\left( x \right)\,dx}}\end{align*}\]

    To prove the formula for “-” we can either redo the above work with a minus sign instead of a plus sign or we can use the fact that we now know this is true with a plus and using the properties proved above as follows.

    \[\begin{align*}\int_{{\,a}}^{{\,b}}{{f\left( x \right) - g\left( x \right)\,dx}} & = \int_{{\,a}}^{{\,b}}{{f\left( x \right) + \left( { - g\left( x \right)} \right)\,dx}}\\ & = \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} + \int_{{\,a}}^{{\,b}}{{\left( { - g\left( x \right)} \right)\,dx}}\\ & = \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} - \int_{{\,a}}^{{\,b}}{{g\left( x \right)\,dx}}\end{align*}\]
    Separator

    Proof of : \(\int_{{\,a}}^{{\,b}}{{c\,dx}} = c\left( {b - a} \right)\), \(c\) is any number.

    If we define \(f\left( x \right) = c\) then from the definition of the definite integral we have,

    \[\begin{align*}\int_{{\,a}}^{{\,b}}{{c\,dx}} & = \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}}\\ & = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} \hspace{0.25in}\hspace{0.25in}\Delta x = \frac{{b - a}}{n}\\ & = \mathop {\lim }\limits_{n \to \infty } \left( {\sum\limits_{i = 1}^n c } \right)\frac{{b - a}}{n}\\ & = \mathop {\lim }\limits_{n \to \infty } \left( {cn} \right)\frac{{b - a}}{n}\\ & = \mathop {\lim }\limits_{n \to \infty } c\left( {b - a} \right)\\ & = c\left( {b - a} \right)\end{align*}\]
    Separator

    Proof of : If\(f\left( x \right) \ge 0\) for \(a \le x \le b\) then \(\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} \ge 0\).

    From the definition of the definite integral we have,

    \[\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} \hspace{0.25in}\hspace{0.25in}\Delta x = \frac{{b - a}}{n}\]

    Now, by assumption \(f\left( x \right) \ge 0\) and we also have \(\Delta x > 0\) and so we know that

    \[\sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} \ge 0\]

    So, from the basic properties of limits we then have,

    \[\mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} \ge \mathop {\lim }\limits_{n \to \infty } 0 = 0\]

    But the left side is exactly the definition of the integral and so we have,

    \[\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} \ge 0\]
    Separator

    Proof of : If \(f\left( x \right) \ge g\left( x \right)\) for\(a \le x \le b\) then \(\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} \ge \int_{{\,a}}^{{\,b}}{{g\left( x \right)\,dx}}\).

    Since we have \(f\left( x \right) \ge g\left( x \right)\) then we know that \(f\left( x \right) - g\left( x \right) \ge 0\)on \(a \le x \le b\) and so by Property 8 proved above we know that,

    \[\int_{{\,a}}^{{\,b}}{{f\left( x \right) - g\left( x \right)\,dx}} \ge 0\]

    We also know from Property 4 that,

    \[\int_{{\,a}}^{{\,b}}{{f\left( x \right) - g\left( x \right)\,dx}} = \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} - \int_{{\,a}}^{{\,b}}{{g\left( x \right)\,dx}}\]

    So, we then have,

    \[\begin{align*}\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} - \int_{{\,a}}^{{\,b}}{{g\left( x \right)\,dx}} & \ge 0\\ \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} & \ge \int_{{\,a}}^{{\,b}}{{g\left( x \right)\,dx}}\end{align*}\]
    Separator

    Proof of : If \(m \le f\left( x \right) \le M\) for \(a \le x \le b\) then \(m\left( {b - a} \right) \le \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} \le M\left( {b - a} \right)\).

    Given \(m \le f\left( x \right) \le M\) we can use Property 9 on each inequality to write,

    \[\int_{{\,a}}^{{\,b}}{{m\,dx}} \le \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} \le \int_{{\,a}}^{{\,b}}{{M\,dx}}\]

    Then by Property 7 on the left and right integral to get,

    \[m\left( {b - a} \right) \le \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} \le M\left( {b - a} \right)\]
    Separator

    Proof of : \(\left| {\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}}} \right| \le \int_{{\,a}}^{{\,b}}{{\left| {f\left( x \right)\,} \right|dx}}\)

    First let’s note that we can say the following about the function and the absolute value,

    \[ - \left| {f\left( x \right)} \right| \le f\left( x \right) \le \left| {f\left( x \right)} \right|\]

    If we now use Property 9 on each inequality we get,

    \[\int_{{\,a}}^{{\,b}}{{ - \left| {f\left( x \right)} \right|\,dx}} \le \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} \le \int_{{\,a}}^{{\,b}}{{\left| {f\left( x \right)} \right|\,dx}}\]

    We know that we can factor the minus sign out of the left integral to get,

    \[ - \int_{{\,a}}^{{\,b}}{{\left| {f\left( x \right)} \right|\,dx}} \le \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} \le \int_{{\,a}}^{{\,b}}{{\left| {f\left( x \right)} \right|\,dx}}\]

    Finally, recall that if \(\left| p \right| \le b\) then \( - b \le p \le b\) and of course this works in reverse as well so we then must have,

    \[\left| {\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}}} \right| \le \int_{{\,a}}^{{\,b}}{{\left| {f\left( x \right)\,} \right|dx}}\]
    Separator

    Fundamental Theorem of Calculus, Part I

    If \(f\left( x \right)\) is continuous on \(\left[ {a,b} \right]\) then,

    \[g\left( x \right) = \int_{{\,a}}^{{\,x}}{{f\left( t \right)\,\,dt}}\]

    is continuous on \(\left[ {a,b} \right]\) and it is differentiable on \(\left( {a,b} \right)\) and that,

    \[g'\left( x \right) = f\left( x \right)\]

    Proof

    Suppose that \(x\) and \(x + h\) are in \(\left( {a,b} \right)\). We then have,

    \[g\left( {x + h} \right) - g\left( x \right) = \int_{{\,a}}^{{\,x + h}}{{f\left( t \right)\,\,dt}} - \int_{{\,a}}^{{\,x}}{{f\left( t \right)\,\,dt}}\]

    Now, using Property 5 of the Integral Properties we can rewrite the first integral and then do a little simplification as follows.

    \[\begin{align*}g\left( {x + h} \right) - g\left( x \right) = \left( {\int_{{\,a}}^{{\,x}}{{f\left( t \right)\,\,dt}} + \int_{{\,x}}^{{\,x + h}}{{f\left( t \right)\,\,dt}}} \right) - \int_{{\,a}}^{{\,x}}{{f\left( t \right)\,\,dt}}\\ & = \int_{{\,x}}^{{\,x + h}}{{f\left( t \right)\,\,dt}}\end{align*}\]

    Finally assume that \(h \ne 0\) and we get,

    \[\begin{equation}\frac{{g\left( {x + h} \right) - g\left( x \right)}}{h} = \frac{1}{h}\int_{{\,x}}^{{\,x + h}}{{f\left( t \right)\,\,dt}} \label{eq:eq1} \end{equation}\]

    Let’s now assume that \(h > 0\) and since we are still assuming that \(x + h\) are in \(\left( {a,b} \right)\) we know that \(f\left( x \right)\) is continuous on \(\left[ {x,x + h} \right]\) and so by the Extreme Value Theorem we know that there are numbers \(c\) and \(d\) in \(\left[ {x,x + h} \right]\) so that \(f\left( c \right) = m\) is the absolute minimum of \(f\left( x \right)\) in \(\left[ {x,x + h} \right]\) and that \(f\left( d \right) = M\) is the absolute maximum of \(f\left( x \right)\) in \(\left[ {x,x + h} \right]\).

    So, by Property 10 of the Integral Properties we then know that we have,

    \[mh \le \int_{{\,x}}^{{\,x + h}}{{f\left( t \right)\,dt}} \le Mh\]

    Or,

    \[f\left( c \right)h \le \int_{{\,x}}^{{\,x + h}}{{f\left( t \right)\,dt}} \le f\left( d \right)h\]

    Now divide both sides of this by h to get,

    \[f\left( c \right) \le \frac{1}{h}\int_{{\,x}}^{{\,x + h}}{{f\left( t \right)\,dt}} \le f\left( d \right)\]

    and then use \(\eqref{eq:eq1}\) to get,

    \[\begin{equation}f\left( c \right) \le \frac{{g\left( {x + h} \right) - g\left( x \right)}}{h} \le f\left( d \right) \label{eq:eq2} \end{equation}\]

    Next, if \(h < 0\) we can go through the same argument above except we’ll be working on \(\left[ {x + h,x} \right]\) to arrive at exactly the same inequality above. In other words, \(\eqref{eq:eq2}\) is true provided \(h \ne 0\).

    Now, if we take \(h \to 0\) we also have \(c \to x\) and \(d \to x\) because both \(c\) and \(d\) are between \(x\) and \(x + h\). This means that we have the following two limits.

    \[\mathop {\lim }\limits_{h \to 0} f\left( c \right) = \mathop {\lim }\limits_{c \to x} f\left( c \right) = f\left( x \right)\hspace{0.25in}\hspace{0.25in}\hspace{0.25in}\mathop {\lim }\limits_{h \to 0} f\left( d \right) = \mathop {\lim }\limits_{d \to x} f\left( d \right) = f\left( x \right)\]

    The Squeeze Theorem then tells us that,

    \[\begin{equation}\mathop {\lim }\limits_{h \to 0} \frac{{g\left( {x + h} \right) - g\left( x \right)}}{h} = f\left( x \right) \label{eq:eq3} \end{equation}\]

    but the left side of this is exactly the definition of the derivative of \(g\left( x \right)\) and so we get that,

    \[g'\left( x \right) = f\left( x \right)\]

    So, we’ve shown that \(g\left( x \right)\) is differentiable on \(\left( {a,b} \right)\).

    Now, the Theorem at the end of the Definition of the Derivative section tells us that\(g\left( x \right)\) is also continuous on \(\left( {a,b} \right)\). Finally, if we take \(x = a\) or \(x = b\) we can go through a similar argument we used to get \(\eqref{eq:eq3}\) using one-sided limits to get the same result and so the theorem at the end of the Definition of the Derivative section will also tell us that \(g\left( x \right)\) is continuous at \(x = a\) or \(x = b\) and so in fact \(g\left( x \right)\) is also continuous on \(\left[ {a,b} \right]\).

    Separator

    Fundamental Theorem of Calculus, Part II

    Suppose \(f\left( x \right)\) is a continuous function on \(\left[ {a,b} \right]\) and also suppose that \(F\left( x \right)\) is any anti-derivative for \(f\left( x \right)\). Then,

    \[\int_{{\,a}}^{{\,b}}{{f\left( x \right)dx}} = \left. {F\left( x \right)} \right|_a^b = F\left( b \right) - F\left( a \right)\]

    Proof

    First let \(g\left( x \right) = \int_{{\,a}}^{{\,x}}{{f\left( t \right)\,\,dt}}\) and then we know from Part I of the Fundamental Theorem of Calculus that \(g'\left( x \right) = f\left( x \right)\) and so \(g\left( x \right)\) is an anti-derivative of \(f\left( x \right)\) on \(\left[ {a,b} \right]\). Further suppose that \(F\left( x \right)\) is any anti-derivative of \(f\left( x \right)\) on \(\left[ {a,b} \right]\) that we want to choose. So, this means that we must have,

    \[g'\left( x \right) = F'\left( x \right)\]

    Then, by Fact 2 in the Mean Value Theorem section we know that \(g\left( x \right)\) and \(F\left( x \right)\) can differ by no more than an additive constant on \(\left( {a,b} \right)\). In other words, for \(a < x < b\) we have,

    \[F\left( x \right) = g\left( x \right) + c\]

    Now because \(g\left( x \right)\) and \(F\left( x \right)\) are continuous on \(\left[ {a,b} \right]\), if we take the limit of this as \(x \to {a^ + }\) and \(x \to {b^ - }\) we can see that this also holds if \(x = a\) and \(x = b\).

    So, for \(a \le x \le b\)we know that \(F\left( x \right) = g\left( x \right) + c\). Let’s use this and the definition of \(g\left( x \right)\) to do the following.

    \[\begin{align*}F\left( b \right) - F\left( a \right) & = \left( {g\left( b \right) + c} \right) - \left( {g\left( a \right) + c} \right)\\ & = g\left( b \right) - g\left( a \right)\\ & = \int_{{\,a}}^{{\,b}}{{f\left( t \right)\,\,dt}} + \int_{{\,a}}^{{\,a}}{{f\left( t \right)\,\,dt}}\\ & = \int_{{\,a}}^{{\,b}}{{f\left( t \right)\,\,dt}} + 0\\ & = \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,\,dx}}\end{align*}\]

    Note that in the last step we used the fact that the variable used in the integral does not matter and so we could change the \(t\)’s to \(x\)’s.

    Separator

    Average Function Value

    The average value of a function \(f\left( x \right)\) over the interval \(\left[ {a,b} \right]\) is given by,

    \[{f_{avg}} = \frac{1}{{b - a}}\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}}\]

    Proof

    We know that the average value of \(n\) numbers is simply the sum of all the numbers divided by \(n\) so let’s start off with that. Let’s take the interval \(\left[ {a,b} \right]\) and divide it into \(n\) subintervals each of length,

    \[\Delta x = \frac{{b - a}}{n}\]

    Now from each of these intervals choose the points \(x_1^*,x_2^*, \ldots ,x_n^*\) and note that it doesn’t really matter how we choose each of these numbers as long as they come from the appropriate interval. We can then compute the average of the function values \(f\left( {x_1^*} \right),f\left( {x_2^*} \right), \ldots ,f\left( {x_n^*} \right)\) by computing,

    \[\begin{equation}\frac{{f\left( {x_1^*} \right) + f\left( {x_2^*} \right) + \cdots + f\left( {x_n^*} \right)}}{n} \label{eq:eq4} \end{equation}\]

    Now, from our definition of \(\Delta x\) we can get the following formula for \(n\).

    \[n = \frac{{b - a}}{{\Delta x}}\]

    and we can plug this into \(\eqref{eq:eq4}\) to get,

    \[\begin{align*}\frac{{f\left( {x_1^*} \right) + f\left( {x_2^*} \right) + \cdots + f\left( {x_n^*} \right)}}{{\frac{{b - a}}{{\Delta x}}}} & = \frac{{\left[ {f\left( {x_1^*} \right) + f\left( {x_2^*} \right) + \cdots + f\left( {x_n^*} \right)} \right]\Delta x}}{{b - a}}\\ & = \frac{1}{{b - a}}\left[ {f\left( {x_1^*} \right)\Delta x + f\left( {x_2^*} \right)\Delta x + \cdots + f\left( {x_n^*} \right)\Delta x} \right]\\ & = \frac{1}{{b - a}}\sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} \end{align*}\]

    Let’s now increase \(n\). Doing this will mean that we’re taking the average of more and more function values in the interval and so the larger we chose \(n\) the better this will approximate the average value of the function.

    If we then take the limit as \(n\) goes to infinity we should get the average function value. Or,

    \[{f_{avg}} = \mathop {\lim }\limits_{n \to \infty } \frac{1}{{b - a}}\sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} = \frac{1}{{b - a}}\,\,\,\mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 1}^n {f\left( {x_i^*} \right)\Delta x} \]

    We can factor the \(\frac{1}{{b - a}}\) out of the limit as we’ve done and now the limit of the sum should look familiar as that is the definition of the definite integral. So, putting in definite integral we get the formula that we were after.

    \[{f_{avg}} = \frac{1}{{b - a}}\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}}\]
    Separator

    The Mean Value Theorem for Integrals

    If \(f\left( x \right)\) is a continuous function on \(\left[ {a,b} \right]\) then there is a number \(c\) in \(\left[ {a,b} \right]\) such that,

    \[\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} = f\left( c \right)\left( {b - a} \right)\]

    Proof

    Let’s start off by defining,

    \[F\left( x \right) = \int_{{\,a}}^{{\,x}}{{f\left( t \right)\,dt}}\]

    Since \(f\left( x \right)\) is continuous we know from the Fundamental Theorem of Calculus, Part I that \(F\left( x \right)\) is continuous on \(\left[ {a,b} \right]\), differentiable on \(\left( {a,b} \right)\) and that \(F'\left( x \right) = f\left( x \right)\).

    Now, from the Mean Value Theorem we know that there is a number \(c\) such that \(a < c < b\) and that,

    \[F\left( b \right) - F\left( a \right) = F'\left( c \right)\left( {b - a} \right)\]

    However, we know that \(F'\left( c \right) = f\left( c \right)\) and,

    \[F\left( b \right) = \int_{{\,a}}^{{\,b}}{{f\left( t \right)\,dt}} = \int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}}\hspace{0.25in}\hspace{0.25in}F\left( a \right) = \int_{{\,a}}^{{\,a}}{{f\left( t \right)\,dt}} = 0\]

    So, we then have,

    \[\int_{{\,a}}^{{\,b}}{{f\left( x \right)\,dx}} = f\left( c \right)\left( {b - a} \right)\]
    Separator

    Work

    The work done by the force \(F\left( x \right)\) (assuming that \(F\left( x \right)\) is continuous) over the range \(a \le x \le b\) is,

    \[W = \int_{{\,a}}^{{\,b}}{{F\left( x \right)\,dx}}\]

    Proof

    Let’s start off by dividing the range \(a \le x \le b\) into \(n\) subintervals of width \(\Delta x\) and from each of these intervals choose the points \(x_1^*,x_2^*, \ldots ,x_n^*\).

    Now, if \(n\) is large and because \(F\left( x \right)\) is continuous we can assume that \(F\left( x \right)\) won’t vary by much over each interval and so in the \(i\)th interval we can assume that the force is approximately constant with a value of \(F\left( x \right) \approx F\left( {x_i^*} \right)\). The work on each interval is then approximately,

    \[{W_i} \approx F\left( {x_i^*} \right)\Delta x\]

    The total work over \(a \le x \le b\) is then approximately,

    \[W \approx \sum\limits_{i = 1}^n {{W_i}} = \sum\limits_{i = 0}^n {F\left( {x_i^*} \right)\Delta x} \]

    Finally, if we take the limit of this as \(n\) goes to infinity we’ll get the exact work done. So,

    \[W = \mathop {\lim }\limits_{n \to \infty } \sum\limits_{i = 0}^n {F\left( {x_i^*} \right)\Delta x} \]

    This is, however, nothing more than the definition of the definite integral and so the work done by the force \(F\left( x \right)\) over \(a \le x \le b\) is,

    \[W = \int_{{\,a}}^{{\,b}}{{F\left( x \right)\,dx}}\]
    亚洲欧美中文日韩视频 - 视频 - 在线观看 - 影视资讯 - av网 <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <文本链> <文本链> <文本链> <文本链> <文本链> <文本链>